Understanding the Belt and Road Initiative - Bhattarai, Dinesh (Journal of APF Command and Staff College, 2019)
China’s project of the century- Belt and Road Initiative - is a signature foreign policy project of President Xi Jinping. Launched in 2013, BRI contains two components- overland belt connecting China with Central Asia, Russia, South Asia and Europe, and Maritime Silk Road for enhancing connectivity, and maritime cooperation linking Chinese ports with Southeast Asia, South Asia, Africa, the Middle East and Europe. BRI wraps up these two initiatives in it and intends to cover the number of countries along the route that happens to be the biggest market in the world with enormous potentials for trade and investment cooperation. BRI has both economic and strategic messages behind a massive infrastructure plan covering a vast network of connectivity linking 60 countries. BRI has sparked a variety of responses, some welcoming and supporting it, some expressing reservations, some willing to participate “for shaping the outcome from within”, and some wanting it to firmly match the international standards of transparency, openness, and the fiscal soundness of the country. Nepal formally became a part of BRI by signing a Memorandum of Understanding on Framework Agreement in May 2017 for enhancing more connectivity and integration, though Nepal is not included in any of the six economic corridors unveiled by China. China recently suggesting Nepal to trim projects from 35 to 9 reflects the standard of the work done by the Nepali government and its lack of preparedness and seriousness. Infrastructure development is key to progress and prosperity. As China remains engaged in improving connectivity in the neighborhood, there is a great optimism about BRI in Nepal. Against this background, this article looks at the significance of BRI, examines past attempts made at connectivity, responses to BRI and Nepal's participation in it.